Unexpected and Habit Driven: Perspectives of Working from Home during the Covid-19 Pandemic - Irawanto, Dodi Wirawan (APMBA (Asia Pacific Management and Business Application), 2020)
No one in the world are expecting this Covid-19 pandemic, impacting mostly on the healthy issue, economic issue, social issue and much more that human being never thought about it. In the white cellar worker, working from home now is a necessity, not just about bringing work to home but many issues raise during this working condition. One of the issues raises is about productivity. For workers that used to work remotely using technology they don’t feel any issues, however, on the others hand for those just enter this new work style, it might be a problem. Telecommuting work have been getting popularity in the late 1980s, mostly this way of work is in respond to many issues in the develop country. As it may too early to conclude where telecommuting and work from home is an apple to apple comparison, as far as the research done in the past, it may can be concluded that the essence is the same. However, little research have been done in the past decade for looking at the telecommuting productivity especially the developing countries. This unexpected event (Covid-19) forces white cellar worker working from home, regardless what type of organization they work for. It may create new work habit, perhaps promote work life balance better for some, or maybe on the other hand bring new productivity issues. It is important in this occasion, that APMBA will open special issue for August 2020 issue to encourage scholars around the world to submit their paper consist of ideas regarding working from home issues. With this editorial note, I would like also to congratulate four paper that addressing marketing, entrepreneurship, operation and finance issue resulted from the 3rd AICMBS conference which was held in October 2019 that coloring the research dissemination through this scholarly venue.